Panorama da graduação em organização da cultura no Brasil - Costa, Leonardo (Políticas Culturais em Revista, 2011)
RESUMO: Buscaremos neste artigo evidenciar a relação da formação em organização da cultura no Brasil através de um panorama do ensino superior, mas especificamente de cursos de graduação plena. Essa escolha se deu devido ao maior grau de continuidade e relevância dessas experiências no contexto da formação, algo fundamental para desenvolver e consolidar uma área acadêmica e profissional. PALAVRAS-CHAVE: Formação. Organização da cultura. Graduação. Viewpoint of the undergraduate courses in the organization of culture in Brazil ABSTRACT: In this article we seek to outline the relationship between the training and qualifications in the organization of culture in Brazil through a viewpoint of the undergraduate courses, but more specifically the full bachelor degree courses. This choice was made due to the higher level of continuity and relevance of these experiences in the context of training, which is central in order to develop and consolidate the academic and professional area. KEYWORDS: Training. Organization of culture. Undergraduate.